Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.